(untitled) (Applied Biological Research, 2015)
An efficient protocol for protocorm like bodies (PLBs) was development and its regeneration through direct somatic embryogenesis was standardized for Rhynchostylis retusa (L.). Somatic embryos were developed from leaf and roots and cultured in MS medium supplemented with different combinations of phytohormones either individually or in combination. The embryo induction was highest in leaf (75%) and root (50.2%) when a combination of 1.0 mg L-1 BAP + 1.5 mg L-1 kinetin was used. Germination of somatic embryos was highest (60%) in ½MS medium with 1.5 mg L-1 BAP. The effect of different PGRs was observed on multiple shoot induction. Maximum number (10.20 ± 0.58) and highest length (3.8 cm) of multiple shoots was observed in MS medium + 1.5 mg L-1 BAP and 1.0 mg L-1 NAA. Highest number (5.8) and length (4.17 cm) of adventitious roots were seen in ½MS medium + 0.5 mg L-1 IAA and 0.5 mg L-1 IBA. The well rooted plants were successfully hardened to the pots that contained small brick pieces, wood charcoal (1:3) and coconut husk; and eventually transferred to shade house for establishment. Plants showed 60% survival.